1969
DOI: 10.1103/physrev.183.7
|View full text |Cite
|
Sign up to set email alerts
|

Annihilation of Positrons in Argon I. Experimental

Abstract: carried out MPHF and optimized-spin-function studies on Li( 2 S) ^nw*,> 1 J L. 1 r , D = 9.3 Amagats E / D = 0.0 J 2.74nsec/Channel \

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1974
1974
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…The larger errors at the lower density are a consequence of the greatly reduced rate of data acquisition which, at = 1 gas event/s, necessitated runs of greater than 600 ks duration. As shown in figure 4 the results obtained for the lowest Ar density agree reasonably well with the earlier measurements of Orth and Jones (1969) and Lee and Jones (1974).…”
Section: Zeff(epsupporting
confidence: 90%
See 4 more Smart Citations
“…The larger errors at the lower density are a consequence of the greatly reduced rate of data acquisition which, at = 1 gas event/s, necessitated runs of greater than 600 ks duration. As shown in figure 4 the results obtained for the lowest Ar density agree reasonably well with the earlier measurements of Orth and Jones (1969) and Lee and Jones (1974).…”
Section: Zeff(epsupporting
confidence: 90%
“…The difference between the observed and the calculated behaviour of ~, p is probably due to the fact that, in the experiment, e+ can be slowed down by inelastic collisions to any energy below the positronium formation threshold (17.8 eV) such that they can have initial energies both above and below the position of the Ramsauer minimum (21.5 eV), whilst Shizgal and Ness (1987) assumed the initial e+ energy distribution to be a delta function at 1 eV. No theoretical calculations of T~ in Ar have been performed for E,, # 0, but the present values support the observations of Orth and Jones (1969) who found that ~, p was not markedly changed on the application of an electric field. The nearly constant value of ~~p is not expected on the basis of the He and Ne work of Shizgal and Ness (1987) who in both cases found rapid shortening of the shoulder as E,, is increased to 10 V cm-' amagat-'.…”
Section: Zeff(epsupporting
confidence: 62%
See 3 more Smart Citations